Synergy between Land Deed Officials and the Regional Revenue Agency of Samarinda City Regarding Determination of Land and Building Sale and Purchase Transaction Values in Samarinda City - Salim, Tandy Setiawan (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
This research aims to examine and analyze the form of synergy between PPAT and the Samarinda City Bapenda Office regarding determining the value of land and building sale and purchase transactions in Samarinda City and examine and analyze the obstacles and constraints that occur in the process of implementing BPHTB collection and determination regarding sale and purchase transactions at the Office. Bapenda Kota Samarinda This research is empirical legal research, namely legal research carried out by conducting field research by looking at and observing what happens in the field, the application of these regulations in practice in society. The results of the research explain that the Land Deed Making Officer (PPAT) is obliged to ask the parties the correctness of the BPHTB tax payment, if the parties as taxpayers cannot submit proof of BPHTB tax payment, because the taxpayer does not know the BPHTB tax and does not know how to calculate the BPHTB payment. , then the Land Deed Drafting Officer (PPAT) has the authority to assist taxpayers in calculating, assist taxpayers in carrying out BPHTB Verification, and supervise BPHTB tax payments made by the taxpayer